Executive leadership in Anglo-American systems - Campbell, Colin, 1943 June 10-; Wyszomirski, Margaret Jane (University of Pittsburgh Press, 1991)
In this collection, eighteen distinguished scholars and practicing officials address the problems of contemporary executive leadership in the United States, Britain, Canada, and Australia. Essays focus on cabinet government; domestic, military, and economic advisers; executive agencies; and personal staff for presidents and prime ministers. Provocative comparisons between and among systems make the discussions particularly insightful.
Keywords: Presidents -- United States.; Presidents -- United States -- Staff.; Executive departments -- United States.; Cabinet system -- Great Britain.; Cabinet system -- Canada.; Comparative government.; Presidents -- United States -- Employees.; Présidents -- États-Unis.; Présidents -- États-Unis -- Personnel.; Ministères -- États-Unis.; Cabinet -- Grande-Bretagne.; Cabinet -- Canada.; Institutions politiques comparées.; comparative politics.; POLITICAL SCIENCE / General; Cabinet system; Comparative government; Executive departments; Presidents; Presidents -- Staff; Canada; Great Britain; United States; Aufsatzsammlung; Regierung; Angloamerika; Political structure and processes; Central government; Aufsatzsammlung.